2022
DOI: 10.1111/jam.15440
|View full text |Cite
|
Sign up to set email alerts
|

Propolis antibacterial and antioxidant synergisms with gentamicin and honey

Abstract: Aims: Assess the antibacterial and antioxidant effects of ethanol extracts of Portuguese propolis samples when combined with gentamicin, a widely used aminoglycoside antibiotic, or with honey, collected from the same apiary as propolis. Methods and Results:Using the agar dilution method and DPPH free radical scavenging assay, antimicrobial and antioxidant synergistic effects between propolis and gentamicin or honey were assessed. Synergism between propolis and gentamicin was observed for all the tested extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 61 publications
0
26
0
4
Order By: Relevance
“…A curious observation from all of these results is that P14.EE, one of the extracts with the lowest TPC and TFC ( Table 1 ) and antioxidant capacity ( Table 2 ) was the one with the highest antibacterial activity ( Table 3 ) but did not have a high anti-yeast activity ( Table 4 ), where typically P15.EE and P15.EE-mixtures excel. This seems to suggest that propolis mode of action against bacteria is not as tightly related to its level of polyphenols and flavonoids contents per se, but possibly is related to certain combinations of compounds or specific synergisms, as has been reported [ 43 ].…”
Section: Resultsmentioning
confidence: 71%
“…A curious observation from all of these results is that P14.EE, one of the extracts with the lowest TPC and TFC ( Table 1 ) and antioxidant capacity ( Table 2 ) was the one with the highest antibacterial activity ( Table 3 ) but did not have a high anti-yeast activity ( Table 4 ), where typically P15.EE and P15.EE-mixtures excel. This seems to suggest that propolis mode of action against bacteria is not as tightly related to its level of polyphenols and flavonoids contents per se, but possibly is related to certain combinations of compounds or specific synergisms, as has been reported [ 43 ].…”
Section: Resultsmentioning
confidence: 71%
“…According to previous research [ 31 , 62 ], the combination of different honeys with propolis extracts from Spain and Poland resulted in the degradation of the sensory properties of the mixtures, but also showed a noteworthy increase in their polyphenolic content and antioxidant activity, with the antimicrobial activity also increasing in some mixtures. In another recent study, propolis and honey mixtures were also found to display a stronger antibacterial effect than the activity exhibited by each individual sample, whereas the high antioxidant capacity of propolis was not affected when used in parallel with honey [ 30 ]. In another study which concurrently employed starch and honey [ 63 ], the addition of starch to five different honey samples increased their antimicrobial properties against Pseudomonas aeruginosa , an opportunistic and pathogenic bacterium well-known for its multidrug resistance and association with some serious hospital-acquired infections [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, research on these two substances has until now tended to focus on them individually and independently of each other. Nevertheless, there are still some promising data on the synergistic biological effects of the combined use of these two hive products, either alone or together with other bioactive compounds (e.g., antibiotics) [ 29 , 30 , 31 ]. Such a combined action could further increase their functional properties and also lower their minimum effective concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the sample collected in Montalegre (north of Portugal) exhibited a scavenging activity effect with an EC 50 value of 10 µg/mL. According to Freitas et al [ 62 ], G18.EE has an EC 50 value of 12.40 ± 0.43 µg/mL. This value was calculated in 2018, the sample’s harvest year.…”
Section: Discussionmentioning
confidence: 99%
“…Fractionation of propolis from Gerês was performed as previously described by Ana Freitas [ 62 ]. Briefly, 4 g of G18.EE was dissolved in 20 mL of absolute ethanol and, after becoming a homogenous solution, 200 mL of purified water were added.…”
Section: Methodsmentioning
confidence: 99%